2020
DOI: 10.1097/pec.0000000000002123
|View full text |Cite
|
Sign up to set email alerts
|

Role of Troponin Determination to Diagnose Chest Pain in the Pediatric Emergency Department

Abstract: Objectives: Chest pain is a common cause to admission to the pediatric emergency department and often leads to an extensive cardiac evaluation. The objective of this study was to evaluate the usefulness of the troponin (TN) plasma level determination in the initial phase of the differential diagnosis of chest pain in children.Methods: This is a retrospective observational study on 107 patients, aged 0 to 19 years, admitted for chest pain to the pediatric emergency department of our institution. Demographics, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Pissarra et al reported that obtained ECG results were abnormal in 77.7% of their patients with cardiac etiologies of chest pain, and Lin et al reported that 84.5% of the patients had ECG abnormalities [ 18 , 23 ]. Additionally, Brancato et al reported that 23.2% of their patients’ ECGs were abnormal [ 14 ]. Cardiac causes of chest pain included myocarditis, pericarditis, myopericarditis, myocardial infarction, pulmonary embolism, pneumopericardium, and rhythm disturbances (supraventricular tachycardia, long QT syndrome, premature ventricular contraction).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pissarra et al reported that obtained ECG results were abnormal in 77.7% of their patients with cardiac etiologies of chest pain, and Lin et al reported that 84.5% of the patients had ECG abnormalities [ 18 , 23 ]. Additionally, Brancato et al reported that 23.2% of their patients’ ECGs were abnormal [ 14 ]. Cardiac causes of chest pain included myocarditis, pericarditis, myopericarditis, myocardial infarction, pulmonary embolism, pneumopericardium, and rhythm disturbances (supraventricular tachycardia, long QT syndrome, premature ventricular contraction).…”
Section: Resultsmentioning
confidence: 99%
“…Musculoskeletal chest pain was reported in nine studies with pooled prevalence = (0.357, 95% CI [0.202, 0.512]) [ 14 20 , 22 , 23 ]. I2 and p values were (99.8%, and p > 0.001, respectively) showing that pooled studies were heterogeneous.…”
Section: Resultsmentioning
confidence: 99%
“…The number of imaging studies obtained during ED visits for pediatric chest pain varies widely in the literature, ranging from 16% ( 24 ) to 94% ( 6 ) for CXR, 20% ( 24 ) to 100% ( 25 ) for EKG and 1% ( 2 , 5 ) to 8% ( 24 ) for echocardiograms. While the number of CXR and EKG obtained in our study was within the range reported in the literature, echocardiograms were less frequently obtained in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Only 5 patients had positive echocardiographic results. The major recommendations for treating people with chest pain include a thorough physical examination and a detailed medical history [20][21][22] . If substantial signs and symptoms are found in children with chest pain, help from a qualified pediatrician should be sought.…”
Section: Discussionmentioning
confidence: 99%